RISK FACTORS OF LIFE QUALITY REDUCTION IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS - Vitalii Dubas (Acta Medica Leopoliensia)
It is a known fact that the presence of a chronic disease or chronic pain syndrome reduces the quality of life (QoL). Despite considerable achievements in the diagnostics and treatment of systemic lupus erythematosus (SLE) over the past decades and improvements in the long-term prognosis of patients, many challenges remain unsolved. The investigation of the quality of life can help to comprehensively evaluate patients' health, the effectiveness and safety of treatment and identify other causes of reduced quality of life that are not directly related to the disease.